The Archiving “I”: A Closer Look in the Archives of Writers - Douglas, Jennifer (Archivaria, 2015)
In 2009, in this journal, Heather MacNeil and I published “Arranging the Self: Literary and Archival Perspectives on Writers’ Archives.” Drawing on the critical literature on life writing, the article introduced the concepts of the “archiving ‘I’” and of “coaxers and coercers” to talk about the various agents that shape an archive over time, and to argue that the creation of an archive is a type of performative act. Here, the concepts are examined in more depth, drawing on research in the archives of eight Canadian and American writers, to show how the work of the archiving “I” and of coaxers and coercers affects the development of writers’ archives and to suggest the implications for the development of theory for personal archives. RÉSUMÉ En 2009 Heather MacNeil et moi-même avons publié dans cette revue l’article « Arranging the Self: Literary and Archival Perspectives on Writers’ Archives ». En s’inspirant des écrits scientifiques au sujet du récit de vie, notre texte a introduit les concepts du « "je" qui archive » et des « cajoleurs et des contrôleurs » pour aborder les divers agents qui façonnent les archives au fil du temps et pour déclarer que la création des archives est un type de performance. Ici, les concepts sont explorés davantage, en s’appuyant sur une recherche conduite dans les archives de huit auteurs canadiens et américains, à la fois pour montrer comment le travail du « je » qui archive et des cajoleurs et contrôleurs affecte le développement des archives des auteurs et pour avancer des idées sur l’implication que cela peut avoir pour l’élaboration de la théorie sur les archives personnelles.